The Loop 'n' Tack Knot: Biomechanical Analysis of a Novel Suture Technique for Proximal Biceps Tenodesis. Issue 9 (23rd September 2020) - Acosta, Jonathan; Rinaldi, John M.; Guth, J. Jared; Akhavan, Sam
Background: Secure tendon grasping is critical to the success of any tenodesis procedure. Several techniques currently used for tendon grasping can result in longitudinal splitting of the tendon, causing construct failure and failure of the tenodesis. Purpose: To compare the Loop 'n' Tack knot as a tendon-grasping technique with other common suture techniques. We investigated the biomechanical strength and mode of failure. Study Design: Controlled laboratory study. Methods: Eleven matched pairs of proximal biceps were harvested from fresh-frozen cadaveric shoulders. One tendon from each pair was stitched using 1 of 4 different techniques. The suture techniques evaluated included the Loop 'n' Tack with 2 different types of high-strength nonabsorbable suture, a double half-racking stitch, and a Krakow stitch. Samples were cyclically loaded between 5 and 20 N for 100 cycles, followed by a pull to failure at 33 mm/s. Results: The Loop 'n' Tack techniques were equivalent to the double half-racking and Krakow techniques for load to ultimate failure ( P = .817 and P = .984, respectively). The double half-racking technique was the stiffest construct, which was significantly greater than the second-stiffest group, the Loop 'n' Tack method with both FiberLink suture ( P = .012) and SutureTape ( P = .002), which had greater stiffness than the Krakow group ( P < .001). The most common failure mode for the Loop 'n' Tack stitch was suture breakage compared with the Krakow and double half-racking methods, where the most common mode of failure was suture pullout from the tendon ( P < .001). Conclusion: Biomechanical testing found that the Loop 'n' Tack techniques had similar ultimate load to failure values when compared with the double half-racking and Krakow methods. Mode-of-failure analysis showed that the Loop 'n' Tack construct typically failed by suture breakage, whereas the other techniques failed by suture pullout. Clinical Relevance: The Loop 'n' Tack technique allows for secure grasping of tissue without the need for externalization of the tendon. This technique may be beneficial in compromised or poor-quality tissue without reducing overall pullout strength when compared with a standard half-racking or Krakow stitch.